Access to Safe, Sustainable, & Healthy Housing in Cambridge Bay, Nunavut: An Institutional Ethnography - Song, Gloria (Université d'Ottawa / University of Ottawa, 2025)
This institutional ethnography examines access to justice issues with respect to the housing crisis in Cambridge Bay, Nunavut, through interviews with 19 community members and 13 service providers, as well as a review of relevant texts including laws and policies. This project provides an original contribution to the field of research in two ways. First, it does so in what was studied, in addressing research needs that has been identified as a priority by Inuit, government, and other actors. Secondly, the project provides an original contribution in how it was studied, in proposing to use institutional ethnography, informed by Inuit Qaujimajatuqangit guidance on research practices, to understand access to justice in Nunavut. The research reveals how the ruling relations perpetuate the ongoing impacts of colonialism with respect to people's housing experiences across the housing continuum. This suggests that a broad, holistic understanding of access to justice is required in Nunavut. The research also challenges the suitability of a western, capitalist, individualist private market-based model of a housing continuum that has been transplanted from southern Canadian jurisdictions, which are grappling with their own housing crises themselves. Instead, it is time to envision a housing model that suits the unique needs of Nunavut and supports goals of Inuit self-determination. --   Cette ethnographie institutionnelle examine les questions d'accès à la justice en ce qui concerne la crise du logement à Cambridge Bay, au Nunavut, au moyen d'entretiens avec 19 membres de la collectivité et 13 fournisseurs de services, ainsi que d'un examen des textes pertinents, y compris les lois et les politiques. Ce projet apporte une contribution originale au domaine de la recherche de deux manières. Premièrement, il le fait au niveau du sujet étudié, en répondant aux besoins de recherche identifiés comme prioritaires par les Inuits, le gouvernement et d'autres parties prenantes. Deuxièmement, le projet apporte une contribution originale dans la manière dont le sujet a été étudié, en proposant d'utiliser l'ethnographie institutionnelle, éclairée par les conseils de l'Inuit Qaujimajatuqangit sur les pratiques de recherche, pour comprendre l'accès à la justice au Nunavut. La recherche révèle comment les relations de pouvoir perpétuent les répercussions actuelles du colonialisme en ce qui concerne les expériences de logement des personnes dans l'ensemble du continuum du logement. Cela suggère qu'il faut envisager une compréhension large et holistique de l'accès à la justice au Nunavut. La recherche remet également en question la pertinence d'un modèle occidental, capitaliste, individualiste et basé sur le marché privé d'un continuum de logement qui a été transplanté des provinces du sud du Canada, qui sont elles-mêmes aux prises avec leurs propres crises du logement. Il est temps d'envisager un modèle de logement qui réponde aux besoins uniques du Nunavut et soutienne les objectifs d'autodétermination des Inuits.
Keywords: access to justice; institutional ethnography; Arctic; Nunavut; Cambridge Bay; Inuit; law; housing